Analysis of the Application of the Tutorial Model on Distance Learning Indonesian Courses at Elementary School Teacher Education, State University of Medan - Rukaiah Proklamasari Hasibuan; Abdurahman Adisaputera; Anita Yus (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aimed to determine the planning, implementation and evaluation of tutorial model on distance learning Indonesian courses in the Elementary School Teacher Education (PGSD) study program, State University of Medan. This research was a descriptive study with a quantitative approach. The data collection in this study was non-participant observation. The instrument used was a questionnaire. The data were analyzed using descriptive percentages. The results showed that the planning tutorial model was significant, realistic, relevant, certain, thorough, adaptable, good time allocation and good planning content. The implementation of tutorial model had been going well and was in accordance with the syntax of the model. The evaluation of tutorial model was in accordance with the learning assessment indicators, namely educational, authentic, objective, accountable, and transparent.